THE ROLE SHARIA FINTECH TO SUPPORT HALAL INDUSTRY IN INDONESIA - ISMAWATI ISMAWATI; TRIMULATO TRIMULATO; MUHLIS MUHLIS; MUSDALIFAH MUSDALIFAH (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2022)
The purpose research to show growth sharia fintech, as well as analysis forms supporting sharia fintech improving halal industry in Indonesia. Research method used qualitative with literature study. Sources data used are secondary data has been presented certain institutions and then processed by researchers. Such as data from Financial Services Authority, Bank Indonesia, and other Data collection techniques used libraries from several sources are considered relevant. Data analysis technique used is descriptive qualitative. Results study indicate development sharia fintech period 2019 to 2020 sharia fintech assets 4.474,86. Sharia fintech lending players 10. Sharia fintech can support development halal industry, with easy access, including Halal SMEs. Multipayment fintech can be a means of payment for business. Sharia fintech Peer to Peer (P2P) Lending will provide access capital, as well as investment facilities. Type sharia crowdfunding fintech provides access joint funds finance halal industry so actors can be helped increase their business.